Events, arguments, and aspects : topics in the semantics of verbs - Robering, Klaus (Studies in language companion series, 2014)
The aspectual interpretation of sentences is constrained by the truth conditions predicates impose on points of times or time intervals. Using data from English, Vendler (1967) established a classification of four verb types on these grounds, that has been widely accepted in linguistic theory. Various researchers, among them Dowty (1979) for English and Ehrich (1992) for German, have proposed finer grained classifications. This paper is very much in the spirit of these proposals. Our aim is a detailed model of the compositional lexical semantics of predicates that models the contrasts of verba.